PENYELESAIAN SENGKETA DANA PENSIUN BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 1992 - Andrew Shandy Utama, (Journal Of Juridische Analyse, 2022)
Pension Fund is a legal entity that manages and runs a program that promises pension benefits. The legal basis that regulates Pension Funds in Indonesia is Law Number 11 of 1992 concerning Pension Funds. The method used in this research is normative legal research. Based on Article 58 of Law Number 11 of 1992 concerning Pension Funds, it is regulated that anyone is prohibited from intentionally causing the payment of an amount of Pension Fund money that deviates from Pension Fund regulations or participating in transactions involving Pension Fund assets. One of the legal problems that occur in the Pension Fund is the misuse of the Pension Fund by the Pension Fund manager. The sanction is a maximum imprisonment of 5 (five) years and a maximum fine of Rp. 5,000,000,000.00 (five billion rupiah).